Evaluation of The Performance of Some Durum Wheat (Triticum durum L.) Genotypes in Organic and Conventional Condition - Remzi ÖZKAN; Cuma AKINCI (ISPEC Journal of Agricultural Sciences, 2021)
The biggest barrier to obtaining high grain yield under organic conditions is nutrient deficiency and weed density. It is predicted that plants with long plant length, early flowering and maturation in wheat can compete better with weeds and give better yield in organic conditions. The study was carried out in the research and application area of Dicle University Faculty of Agriculture in Diyarbakır in rain-fed condition during the 2019-2020 production season. In this study, materials were used as follows: 29 durum wheat genotypes from local cultivars and 3 check cultivars (Sena, Svevo and Eyyubi). The study was set up in 3 blocks (each consisting of 10 rows) according to the augmented experimental design in 2 different experiments (organic and conventional). In the study, it was aimed to evaluate the performance of local genotypes under organic conditions by comparing them with conventional conditions and to determine the appropriate selection parameters for organic wheat breeding. In this study, some physiological, phenological, morphological, yield and quality characteristics were examined. According to the results, early heading genotypes under organic conditions had higher grain yield potential. In addition, the effect of NDVI and LAI values ​​on grain yield was found to be significant. DYM-19, DYM-17, YM-12, UYM-5 and DYM-16 genotypes, which have minimum decrease in grain yield in organic conditions, and Atkı-2 variety, which gives the highest grain yield in both agricultural systems has been determined that they can be used as a parent in breeding studies for organic conditions.